The Effectiveness of STAD Method Towards Students’ Understanding of Simple Present Tense - Hurairo, Eti Widiya; Iman, Jaya Nur; Angraini, Nike Angraini (International Journal of English Education and Linguistics (IJoEEL), 2023)
Understanding grammar is essential for students learning English as a foreign language. Grammar rules provide order and clarity to the language so that students could understand how words, phrases and sentences are combined. According to Ameilani (2019), "Grammar is the most challenging issue, Although I can speak English, I sometimes get confused when arranging words and sentences related to grammar" one participant said. Therefore, the purposes of this study were to ascertain whether there was a significant improvement in student achievement in understanding simple present tense after being taught using the STAD method and to find out whether there was a significant mean difference between students who were taught using the STAD method and those who were not taught using the STAD method. This study used a quasi-experimental design method. 66 students in the eighth grade in SMP Negeri 38 Palembang were chosen by the researcher using the purposive sampling and divided into the experimental and the control classes. Based on the test results using Wilcoxon test, there was a significant improvement in students' achievement in understanding simple present tense after being taught with STAD method. Based on Mann Whitney test, it was also found that there was a significant mean difference between students who were taught using STAD method and those who were not taught using STAD method. In conclusion, the use of STAD method was effective in improving students' understanding at SMP Negeri 38 Palembang.